Opposite malaria and pregnancy effect on oral bioavailability of artesunate - a population pharmacokinetic evaluation. - Kloprogge, F; McGready, R; Phyo, A; Rijken, M; Hanpithakpon, W; Than, H; Hlaing, N; Zin, N; Day, N; White, N; Nosten, F; Tarning, J (Wiley, 2015)
The aim was to compare the pharmacokinetic properties of artesunate and dihydroartemisinin in the same women: i) pregnant with acute uncomplicated malaria on day 1 and 2, ii) pregnant with convalescent malaria on day 7 and iii) in a healthy state 3 months post-partum on day 1, 2 and 7.Non-linear mixed-effects modelling was used to compare plasma concentration-time profiles of artesunate and dihydroartemisinin over 7 days of treatment following oral and intravenous artesunate administration to pregnant women with uncomplicated Plasmodium falciparum malaria during their second or third trimesters of pregnancy. The same women were restudied 3 months after delivery when fully recovered. Non-compartmental results of the same study have been published previously.Twenty pregnant patients on the Thailand-Myanmar border were studied and 15 volunteered to be restudied 3 months post-partum. Malaria and pregnancy had no effect on the pharmacokinetic properties of artesunate or dihydroartemisinin after intravenous artesunate administration. However, malaria and pregnancy had opposite effects on the absorption of orally administered artesunate. Malaria increased the absolute oral bioavailability of artesunate by 87%, presumably by inhibiting first pass effect, whereas pregnancy decreased oral bioavailability by 23%.The population pharmacokinetic analysis demonstrated opposite effects of malaria and pregnancy on the bioavailability of orally administered artesunate. Lower drug exposures during the second and third trimesters of pregnancy may contribute to lower cure rates and thus the development of drug resistance. Dose optimization studies are required for artesunate containing artemisinin-based combination therapies (ACTs) in later pregnancy.